Localization and Global Marketing: Adapting Digital Strategies for Diverse Audiences - Okonkwo, Ifeanyi; Mujinga, John; Namkoisse, Emmanuel; Francisco, Adrien (Journal of Digital Marketing and Communication, 2023)
In an increasingly interconnected world, businesses aiming for global success must navigate the intricate landscape of localization and global marketing. This manuscript delves into the pivotal strategies required to adapt digital marketing approaches, reaching and engaging diverse audiences worldwide. It emphasizes the significance of adapting digital marketing strategies through localization techniques to effectively cater to diverse global audiences. Staying informed is paramount, as a deep understanding of local news, cultural events, and ongoing conversations within a region is essential for creating content that remains timely and relevant. Active engagement in conversations related to local trends amplifies brand visibility and engagement within the community. Collaborating with local influencers provides an authentic bridge to regional audiences, offering valuable insights into the pulse of local trends. Aligning content with local values, interests, and sensitivities ensures that marketing materials resonate positively with diverse audiences. Additionally, the strategic use of localized hashtags enhances content discoverability. Encouraging user-generated content serves a dual purpose: fostering engagement and authentic endorsements, thereby bolstering brand credibility.